Inhibition of metal dusting of alloy 800H by laser surface melting - Voisey, K.T.; Liu, Z.; Stott, F.H. (Elsevier, 2006)
Metal dusting is a catastrophic carburisation phenomenon that occurs at temperatures of 450-850°C in atmospheres of high carbon activity. The resistance of alloys to corrosion, including metal dusting, relies on the formation of a dense, adherent oxide layer that separates the alloy from the corrosive environment. For such an oxide layer to be protective, it must achieve full surface coverage, be crack-free and be established before significant material degradation has occurred. Formation of a protective oxide scale can be enhanced by increasing the population of rapid diffusion paths for the protective elements (e.g. Cr and Al) to reach the alloy surface. In this work, laser surface melting has been used to improve the metal dusting resistance of Alloy 800H by creating a rapid solidification microstructure and, thereby, increasing the density of rapid diffusion paths. Oxidation during laser processing has been found to be detrimental to metal dusting resistance. However, it has been demonstrated that the resulting oxide can be removed without compromising metal dusting resistance. Results of exposure to a metal dusting atmosphere (20% H2 80% CO at 650°C) are presented. Samples have been examined in plan and cross-section using optical and scanning electron microscopy. Selected samples were also examined by electron probe microanalysis and X-ray diffraction.